DEPARTMENTS AND TREATMENT GROUPS AT PENITENTIARY FACILITIES IN SERBIA AND EVALUATION OF PRISON LIFE QUALITY - Ilijić, Ljeposava; Stevanović, Ivana; Vujičić, Nikola (Pravni zapisi, 2024)
The paper addresses the issues pertinent to the relationship between the prison social climate and departments as well as treatment groups at penitentiary facilities (MQPL survey). The focal objective of this paper is to investigate potential differences in how the prison life quality is perceived by persons who reside in different departments and treatment groups. A sample of 616 convicted adult persons was used for this research, which was conducted in 2022. The respondents were serving a prison sentence at penitentiary facilities in Niš, Sremska Mitrovica, Požarevac– Zabela, Belgrade, and the Penitentiary facility for Women in Požarevac. Analysis of variance and descriptive statistics were used. There is a clear pattern in the results of the analysis, namely that person in semi-opened departments rate the quality of prison life significantly better than persons in closed departments. The authors link the obtained results with prison deprivation, risk assessment, and opportunities for improving the prison social climate.